2015
DOI: 10.18512/1980-6477/rbms.v14n2p235-246
|View full text |Cite
|
Sign up to set email alerts
|

Simulação da Necessidade Hídrica e Estimativa de Produtividade para Cultura do Milho em Municípios do RS

Abstract: RESUMO-A produtividade de milho é limitada no estado do Rio Grande do Sul (RS), principalmente pela deficiência hídrica. Este estudo objetivou identificar a lâmina suplementar de irrigação e avaliar sua resposta em produtividade para três municípios do RS em diferentes datas de semeadura. Foram usados dados meteorológicos de uma série de 21 anos (1992-2012), dados de solo dos três locais e informações agronômicas da cultura do milho. Foi usado o modelo WinISAREG para simular a demanda hídrica. Com o uso de uma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 2 publications
0
4
0
9
Order By: Relevance
“…Kopp et al (2015) studied four sowing dates between 1992 to 2012 in three municipalities of RS, and concluded an average water supplement of 393 mm was needed for maize, based on an average reduction of 55.2% in grain yield during the study period. As such, supplementary water was emphasized as one of the techniques necessary to stabilize the production of maize (MINUZZI; RIBEIRO, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Kopp et al (2015) studied four sowing dates between 1992 to 2012 in three municipalities of RS, and concluded an average water supplement of 393 mm was needed for maize, based on an average reduction of 55.2% in grain yield during the study period. As such, supplementary water was emphasized as one of the techniques necessary to stabilize the production of maize (MINUZZI; RIBEIRO, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the same locality, applying supplementay irrigation depths in maize, Pegorare et al (2009) observed that a 510 mm depth increased productivity by up to 130% in relation to the rainfed growth. To test for differences between the water demands of the corn crop in Bagé, Santa Maria and Uruguaiana, Rio Grande do Sul State, at different growing seasons, Kopp et al (2015) verified demands in the order of 531 to 735 mm. Souza et al (2012), in Seropédica, Rio de Janeiro State, observed that, after selection of different cropping systems, "Eldorado" maize cultivar had a total water consumption of 394.1 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Em sequencia, na Figura 2, a evapotranspiração da cultura (ETc) atingiu maior valor acumulado de 591 mm em 15-nov, tal fato deve-se maior disponibilidade de energia associada a maior disponibilidade de água no solo. No Rio Grande do Sul, KÖPP et al (2015), também relacionaram a maior evapotranspiração do milho como consequências das maiores temperaturas e maior insolação quando avaliadas no município de Uruguaiana. A maior necessidade de água via irrigação foi observada em 15 de novembro, quando totalizou 251,2 mm de água aplicada.…”
Section: Resultsunclassified
“…A medida que ocorre o atraso da semeadura, a ETc aumenta, totalizando 620 mm em 15 de novembro, com intervalo de confiança, variando de 572,4 mm a 608,6 mm, evidenciando a variabilidade da disponibilidade hídrica nas datas de semeadura. KÖPP et al (2015), encontraram 654 mm de evapotranspiração média no ciclo, com intervalo de consumo hídrico de 531 a 735 mm.…”
Section: Resultsunclassified